Classical theory of investment: panel cointegration evidence from 13 EU countries - Alexiou, Constantinos; Tsaliki, P.; Tsoulfidis, L. (Oxford University Press, 2016)
In the realm of macroeconomic theory, it is well established that investment decisions play an instrumental role in the determination of the level of output and employment; nevertheless, little progress has been made in relation to the theoretical aspects of these decisions. This paper, inspired by the classical approach to capital accumulation as well as the Keynesian theory of effective demand, attempts to enhance our empirical understanding of what determines investment decisions by exploring profitability, financial as well as demand factors. In so doing, a ‘Fully Modified OLS’ panel cointegration framework, for a cluster of two distinct groups of EU countries classified as core and the peripheral economies, provides the platform upon which our econometric investigation takes place. The respective evidence generated from the estimation process is in line with the theoretical framework proposed in this paper.